The Correlation of Perceived Social Support and Emotional Schemes With Students’ Social Anxiety - Leila Moghtader; Matina Shamloo (Journal of Holistic Nursing and Midwifery)
Introduction: Social anxiety remembered as an annoying experience in the presence of others is one of the most common mental disorders, especially in students. Objective: The current study aimed at determining the relationship between perceived social support and maladaptive emotional schemes with social anxiety in students. Materials and Methods: The current correlational analytic study was conducted on all undergraduate students of Islamic Azad University, Rasht Branch in the academic year of 2015-2016 that was 3986 people. In the current study, 351 students with social anxiety were selected using the convenient sampling method and Morgan table. The study tools included the Zimet perceived social support scale, the Leahy emotional schemes scale, and Jerabek social anxiety questionnaire. The collected data were analyzed using descriptive statistics and Pearson correlation coefficient test. Results: The mean age of students was 22.72±4.80 years according to the results of descriptive information. Most of the participants in the study (80.06%) were single. The mean of social anxiety was 68.01±13.12, social support 43.7±8.70, and emotional scheme 104.33±12.99. The results indicated a negative and significant relationship between perceived social support and social anxiety (r=-0.30, P<0.01). The relationship between emotional schemes and social anxiety was positive and significant (r=0.44, P<0.01). Conclusion: The results indicated that students with higher perceived social support experienced lower social anxiety. Maladaptive emotional schemes can be associated with students’ social anxiety.